КОН’ЮНКТУРНІ ДОСЛІДЖЕННЯ В СИСТЕМІ МАРКЕТИНГОВОГО АНАЛІЗУ - Бабух, Ілона (Publishing House Helvetica (Publications), 2021)
The article considers the peculiarities of market conjuncture in the system of marketing analysis as a component of the marketing complex of the enterprise. The ability to conduct conjuncture research is becoming especially relevant today due to the constant changes in the markets. Market conjuncture is its state or economic situation on it, which is characterized by the ratio of supply and demand, price dynamics, the activity of entities. The conjuncture situation depends on many factors, which must be analyzed in conjuncture research. The main tasks of conjuncture research and the main approaches for its implementation are indicated, a certain sequence of conjuncture research is given. Conjuncture analysis in the marketing system should be conducted ontinuously and systematically, it is a complex intellectual process and requires comprehensive and systematic approaches. If a systems approach is a multi-level or hierarchical description of the market as an object, then within the framework of an integrated approach, the market is considered through the interaction of many factors of the internal and external environment. To study conjuncture conditions, an appropriate system of indicators is developed, which differs for individual types of markets, but in general, based on it, the most complete and systematically real conjuncture situation of a particular market is presented. The stages of conjuncture research are given and the main methods used by marketers in the analysis of market conjuncture are emphasized. Among such methods the most complete and often used are methods of comparison, grouping, visual and graphic. It is mandatory to build time series, more and more experts turn to correlation-regression analysis, as well as the index method. It is also essential for marketing analysis to monitor the factors that affect market conjuncture, among which micro- and macro-level factors are distinguished. Significant among such factors of market conditions is the presence or absence of competition on this market, the product range of its products, the specifics of pricing by competitors. Forecasting the further development of markets as the end result of conjuncture research and the basis of future market behavior completes conjuncture research
Keywords: кон’юнктурні дослідження; маркетинговий аналіз; кон’юнктура ринку; аналіз кон’юнктури; прогноз кон’юнктури; етапи кон’юнктурного дослідження